Does The Covid-19 Pandemic Affect Financing of Islamic Banks in Indonesia? - Achsani, Muhammad Nur Faaiz F; Kassim, Salina; Haron, Razali (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2025)
Introduction: This study investigates the influence of macroeconomic and bank-specific variables on financing activities in Indonesian Islamic banks, particularly during the COVID-19 pandemic, to assess the sector's financial resilience and alignment with sustainable finance principles. Methods: This research employs a quantitative approach using dynamic panel data analysis covering the period from 2011 to 2023, with variables including Gross Domestic Product, inflation, interest rates, non-performing financing, bank size, profitability, and a pandemic indicator. Results: The findings reveal that while the COVID-19 pandemic did not significantly affect financing, interest rates and bank size had a significant positive impact. Other variables such as GDP, inflation, non-performing financing, and profitability did not exhibit statistically significant effects. The resilience observed in Islamic banks is attributed to their reliance on ethical principles, risk-sharing mechanisms, and asset-backed financing structures. Conclusion and suggestion: The study concludes that Indonesian Islamic banks-maintained stability during the pandemic, reinforcing their role in promoting long-term financial sustainability and economic resilience. Policymakers and regulators are encouraged to support the Islamic banking sector as a key component of sustainable finance frameworks, leveraging its unique characteristics to contribute to broader development goals.